Palladium‐Catalyzed Directed C(sp3)–H Arylation of Saturated Heterocycles at C‐3 Using a Concise Optimization Approach. Issue 1 (27th November 2015) - Affron, Dominic P.; Bull, James A.
Abstract: Saturated heterocycles, such as THFs, pyrrolidines, piperidines and THPs, are essential components of many biologically active compounds. Examples of C–H functionalization on these important ring systems remain scarce, especially at unactivated positions. Here we report the development of conditions for the palladium‐catalyzed stereoselective C(sp 3 )–H arylation at unactivated 3‐positions of 5‐ and 6‐membered N‐ and O‐heterocycles with aminoquinoline directing groups. Subtle differences in substrate structures altered their reactivity significantly; and different conditions were required to achieve high yields in each case. Successful conditions were developed using a short empirical optimization approach to cover reaction space with a limited set of variables. Excellent cis ‐selectivity was achieved in all cases, except for the THP substrate where minor trans ‐products were formed through a different palladacyclic intermediate. Here, differences in reactivity and selectivity with other directing groups were examined. Abstract : Making a long story short: cis ‐2, 3‐Functionalized THF, pyrrolidine, piperidine and THP derivatives are synthesized in high yields by Pd‐catalyzed directed C(sp 3 )–H arylation. The subtle differences in substrate classes altered their reactivity considerably, requiring different conditions for each heterocycle. Successful reaction conditions were developed using a programmed optimization approach, employing a limited selection of variables to cover the appropriate reaction space.